Influence Work, Resistance, and Educational Life-Worlds: Quintilian’s [Marcus Fabius Quintilianus] (35-95 CE) Analysis of Roman Oratory as an Instructive Ethnohistorical Resource and Conceptual Precursor of Symbolic Interactionist Scholarship - Prus, Robert (Qualitative Sociology Review, 2022)
Despite the striking affinities of classical Greek and Latin rhetoric with the pragmatist/interactionist analysis of the situated negotiation of reality and its profound relevance for the analysis of human group life more generally, few contemporary social scientists are aware of the exceptionally astute analyses of persuasive interchange developed by Aristotle, Cicero, and Quintilian. Having considered the analyses of rhetoric developed by Aristotle (384-322 BCE) and Cicero (106-43 BCE) in interactionist terms (Prus 2007a; 2010), the present paper examines Quintilian’s (35-95 CE) contributions to the study of persuasive interchange more specifically and the nature of human knowing and acting more generally. Focusing on the education and practices of orators (rhetoricians), Quintilian (a practitioner as well as a distinctively thorough instructor of the craft) provides one of the most sustained, most systematic analyses of influence work and resistance to be found in the literature. Following an overview of Quintilian’s “ethnohistorical” account of Roman oratory, this paper concludes by drawing conceptual parallels between Quintilian’s analysis of influence work and the broader, transcontextual features of symbolic interactionist scholarship (Mead 1934; Blumer 1969; Prus 1996; 1997; 1999; Prus and Grills 2003). This includes “generic social processes” such as: acquiring perspectives, attending to identity, being involved, doing activity, engaging in persuasive interchange, developing relationships, experiencing emotionality, attaining linguistic fluency, and participating in collective events. Offering a great many departure points for comparative analysis, as well as ethnographic examinations of the influence process, Quintilian’s analysis is particularly instructive as he addresses these and related aspects of human knowing, acting, and interchange in highly direct, articulate, and detailed ways. Acknowledging the conceptual, methodological, and analytic affinities of The Institutio Oratoria of Quintilian with symbolic interactionism, an epilogue, Quintilian as an Intellectual Precursor to American Pragmatist Thought and the Interactionist Study of Human Group Life, addresses the relative lack of attention given to classical Greek and Latin scholarship by the American pragmatists and their intellectual progeny, as well as the importance of maintaining a more sustained transcontextual and transhistorical focus on the study of human knowing, acting, and interchange.